Reflections of Urban Existence: Analyzing Mental Life in Gunasekera's The Sandglass - Thapa, Mumaya (NPRC Journal of Multidisciplinary Research, 2025)
Background: Romesh Gunasekera’s The Sandglass (1998) presents the story of the Ducal family who moved to London from Sri Lanka. The narrative builds on the retrospection of the narrator, a lodger at Ducals’ house in London. It demonstrates the strong role of urban space in constructing the psychology and social life of the characters.Methods: Employing Georg Simmel’s idea of mental life in the metropolis, this paper examines the interplay of urban environment and cognitive life in The Sandglass. The novel depicts urban life that reflects Simmel's notion of the blasé attitude. The reserved nature of the characters serves as a coping mechanism in the city, where they navigate the overwhelming stimuli and emotional complexities of their surroundings.Result: Through an analysis of key concepts, such as the commodification of relationships and the tension between individuality and social integration, this study reveals how Gunasekera reflects urbanites’ mental lives. The emphasis on the objective spirit of city dwellers leads to a loss of emotional intimacy and indifference among the residents of urban space. The characters struggle with isolation while seeking meaningful connections in a fragmented society. Their inner lives explicate the challenges of maintaining authenticity in an impersonal urban landscape.Conclusion:The Sandglass weaves themes of modernity and mental health, enriching the discussion on the psychological dimensions of urban existence. The setting and the characters represent the features of the metropolitan mental life discussed by Simmel.Novelty: This study concludes that cities are physical spaces that embody cultural values, social norms, political tensions, and historical narratives, all of which influence how people perceive themselves and their relationships with others.